2008
DOI: 10.1210/er.2007-0037
|View full text |Cite
|
Sign up to set email alerts
|

Islet Amyloid in Type 2 Diabetes, and the Toxic Oligomer Hypothesis

Abstract: Type 2 diabetes (T2DM) is characterized by insulin resistance, defective insulin secretion, loss of beta-cell mass with increased beta-cell apoptosis and islet amyloid. The islet amyloid is derived from islet amyloid polypeptide (IAPP, amylin), a protein coexpressed and cosecreted with insulin by pancreatic beta-cells. In common with other amyloidogenic proteins, IAPP has the propensity to form membrane permeant toxic oligomers. Accumulating evidence suggests that these toxic oligomers, rather than the extrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
564
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 553 publications
(586 citation statements)
references
References 145 publications
20
564
0
2
Order By: Relevance
“…Islet amyloid formation in patients with type 2 diabetes contributes to progressive beta cell death [3][4][5]. Unlike in type 2 diabetes, amyloid forms rapidly in cultured [6][7][8] and transplanted human islets [9,10], and this is associated with beta cell dysfunction and death in vitro [6][7][8], and with islet graft failure leading to recurrence of hyperglycaemia in animal models of type 1 diabetes [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Islet amyloid formation in patients with type 2 diabetes contributes to progressive beta cell death [3][4][5]. Unlike in type 2 diabetes, amyloid forms rapidly in cultured [6][7][8] and transplanted human islets [9,10], and this is associated with beta cell dysfunction and death in vitro [6][7][8], and with islet graft failure leading to recurrence of hyperglycaemia in animal models of type 1 diabetes [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Islet amyloid is typically found extracellular, adjacent to beta cells [6-8, 13, 20, 21], but intracellular hIAPP aggregates also form in humans and transgenic rodent models [9,13,18,21]. Small hIAPP aggregates appear to be the major mediators of beta cell death [3,4,22].…”
Section: Introductionmentioning
confidence: 99%
“…Human amylin's physiological conformation is one of random coil, but it undergoes rapid conformational change into β-conformers when placed in physiological solutions [35]. Based on the available evidence, many workers have concluded that small oligomers formed by aggregated human amylin [36,37] are probably the species that could ultimately cause diabetes [38,39]. Others, among them Zraika and colleagues, believe that the cytotoxicity of larger amyloid fibrils must be considered [11,15], as indeed it must.…”
mentioning
confidence: 99%
“…Zraika et al have argued that mature amyloid fibrils, rather than small, soluble cytotoxic oligomers [37][38][39]43], could play the main role in beta cell degeneration and diabetes causation. As noted, they have pointed to the numerous weaknesses and shortcomings of the currently available evidence, and in so doing have indicated further lines of investigation that might improve our understanding.…”
mentioning
confidence: 99%
See 1 more Smart Citation